mTOR inhibitor introduce disitamab vedotin (RC48-ADC) rechallenge microtubule-chemotherapy resistance in HER2-low MBC patients with PI3K mutation - Hu, Ye; Chen, Fengxi; Sun, Siwen; Xv, Lingzhi; Wang, Xueqing; Wang, Meiling; Zhao, Shanshan; Zhao, Zuowei; Li, Man (Frontiers in Oncology, 2024)
This study aimed to explore the efficacy and potential mechanisms of rechallenge therapy with Microtubule-targeting agents (MTAs) in patients with HER2-low metastatic breast cancer (MBC). We performed a systematic review to investigate the rechallenge treatment concept in the field of HER2-low MBC treatment and utilized a series of cases identified in the literature to illustrate the concept. Here, we reported two clinical cases of HER2-low MBC patients whose disease progressed after prior treatment with MTAs such as docetaxel and vincristine. When rechallenged with Disitamab Vedotin ((RC48-antibody-drug conjugate (ADC), a monomethyl auristatin (MMAE) MTA)), both patients achieved a partial response and the final progression-free survival (PFS) was 13.5 or 9 months, respectively. Genomic profiling detected a PIK3CA H1047R mutation in the patients. Patients were treated with everolimus before being rechallenged with RC48, which may lead to a better response. This study further summarizes and analyzes the potential mechanism of the PI3K-AKT signaling pathway in MTAs resistance and reveals that the PIK3CA H1047R mutation may be a potential molecular marker for the efficacy prediction of mTOR inhibitors, providing new insights and potential therapeutic strategies for the application of MTAs to MBC patients.